URGENSI PENERAPAN ASAS SINGLE PROSECUTION SYSTEM DALAM MEWUJUDKAN KEPASTIAN HUKUM - Mohammad Haikal Dzikrullah; Sri Wahyu Handayani; Abdul Aziz Nasihuddin (Smart Education, 2026)
Abstract: As a state governed by the rule of law, Indonesia establishes law as the primary foundation for achieving legal certainty (*rechtszekerheid*) within the criminal justice system. However, the post-reform era has witnessed a fragmentation of prosecutorial authority resulting from the enactment of various special laws (*lex specialis*) outside the codified Criminal Procedure Code (KUHAP). Prosecutorial authority is now distributed among autonomous institutions such as the Attorney General's Office, the Corruption Eradication Commission (KPK), and the Military Prosecution Service (*Oditurat Militer*). This institutional fragmentation severs the single chain of command, fosters sectoral ego, and creates jurisdictional overlaps, particularly in cases involving joint military-civilian jurisdiction (*koneksitas*). This study aims to analyze the urgency of implementing a